Para além da história local: o protagonismo estudantil na criação do museu das relações étnico-raciais - Rodrigues, André Luiz Henrique Tavares de Melo (2025)
Although there is a considerable body of research on the teaching of Local History, studies focusing on this topic at the high school level are scarce—especially those addressing the perspectives of historically marginalized groups. The aim of this research is to propose a Local History teaching approach that distances itself from official narratives, fostering student protagonism and teaching through cultural practices rooted in Afro and/or Indigenous heritages present in the daily lives of young students. The central issue of this study arises from analyzing the pedagogical potential of the Museum of Ethnic-Racial Relations during the creation of its first exhibition, which was developed by high school students from the rural area of Aracoiaba. Given this, how can this subject be taught within the context of implementing the New High School Curriculum (Novo Ensino Médio - NEM) and the Full-Time Program in Ceará, with limited teaching resources? How should we proceed when faced with a regional historiography of a positivist nature, strongly inclined toward memorialist narratives from urban elite families? To address such meaningful questions, an action-research project was developed in multiple stages. First, students' prior knowledge about local historical narratives was assessed, along with investigations into where they had obtained the information they mentioned. In 2023, a questionnaire was administered to 100 students from the four 2nd-year classes at the João Alves Moreira Full-Time High School (EEMTI JAM). It was observed that about 90% of the students believed that “there was no history” in their places of residence. From this starting point, and aiming to develop diverse teaching resources, scientific research based on historical sources— including written documents, images, and objects—was encouraged. In order to promote student protagonism and comply with Laws 10.639/2003 and 11.645/2008 concerning the teaching and learning of Local History, one of the educational experiences carried out was the establishment of the Museum of Ethnic-Racial Relations in the district of Ideal, in Aracoiaba. The results show that meaningful learning not only provided knowledge about the region's Local History but also fostered critical awareness and student protagonism. Special emphasis was placed on previously silenced narratives, leading to the development of diverse resources using a counter-hegemonic approach. This work offers practical material for teaching Local History that will inspire and support educators from other regions in creating museum exhibitions that promote more pluralistic and democratized pedagogies through a non- Eurocentric lens.